2012
DOI: 10.4236/jsea.2012.53024
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Internal Model Control of a DC Motor Drive System Using Dynamic Neural Network

Abstract: This work concerns the study of problems relating to the adaptive internal model control of DC motor in both cases conventional and neural. The most important aspects of design building blocks of adaptive internal model control are the choice of architectures, learning algorithms, and examples of learning. The choice of parametric adaptation algorithm for updating elements of the conventional adaptive internal model control shows limitations. To overcome these limitations, we chose the architectures of neural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Recently, nonlinear systems have become a research hotspot due to it can better describe the actual system. Usually, the fuzzy or NN technique are used to estimate the nonlinear function in the system, 1–8 and the backstepping control approach is utilized to design the controller 9–14 . Although many excellent research results have been reported, there are still many unsolved problems, such as disturbance and unknown gain function and so forth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, nonlinear systems have become a research hotspot due to it can better describe the actual system. Usually, the fuzzy or NN technique are used to estimate the nonlinear function in the system, 1–8 and the backstepping control approach is utilized to design the controller 9–14 . Although many excellent research results have been reported, there are still many unsolved problems, such as disturbance and unknown gain function and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, the fuzzy or NN technique are used to estimate the nonlinear function in the system, [1][2][3][4][5][6][7][8] and the backstepping control approach is utilized to design the controller. [9][10][11][12][13][14] Although many excellent research results have been reported, there are still many unsolved problems, such as disturbance and unknown gain function and so forth. In Reference 15, for the affine nonlinear systems suffer from disturbances and uncertainties, a full-order observer which joins the ultimate uniform bounded stability and sliding-mode is presented.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] To cope with practical systems with nonlinearities unmatched to local control inputs, the control problems of multiple-input-multiple-output (MIMO) nonlinear systems have been addressed via recursive control techniques. [14][15][16][17] Furthermore, adaptive tracking control approaches have been widely studied for several uncertain nonlinear systems [18][19][20][21] and practical nonlinear systems such as nonlinear servo systems, [22][23][24][25] active suspension systems, 26 direct-current motor drive systems, 27,28 and fractional-order systems. 29 Neural networks and fuzzy logic systems have been employed to compensate for unknown nonparametric uncertainties in approximation-based adaptive containment control schemes of nonlinear multi-agent systems in strict-feedback [30][31][32][33] and pure-feedback forms.…”
Section: Introductionmentioning
confidence: 99%
“…3). As a result, the ERLS algorithm estimates the parameters of the DC motor, which is equivalent to the parameters of (13). Fig.…”
Section: International Journal Of Computer Applications (0975 -8887) mentioning
confidence: 99%
“…These types of controllers are capable to improve the overall response of the controlled system [10]. Different techniques are presented in the literature, for instance the authors in [11,12] apply the fuzzy controller approach for digitally control of DC motor, while in [13][14][15][16] a neural network controller is proposed. Model reference method and adaptive techniques are also demonstrated in [9,17,18].…”
Section: Introductionmentioning
confidence: 99%